REPRESENTASI DALAM MENYELESAIKAN MASALAH BARISAN BERDASARKAN TINGKAT KEMAMPUAN SISWA - Devinta Reza Prasanti; Susiswo Susiswo (Jurnal Kajian Pembelajaran Matematika, 2019)
AbstractThe aim of this research is to describe the representation of solving problem in sequence based on the level of students’ abilities. This research used the qualitative research method with descriptive type. The subject of this research is determined by the result of the pre-requisite knowledge test and interview. The result of this research shows that, in solving problems in sequence, students with high ability use verbal, visual, and symbolic representation. Students with high ability use four steps of problem solving to obtain correct answer. Student with average ability only use verbal and symbolic representation. Student with average ability do not apply the look back step in one of the problems. On the other hand, student with low ability, use verbal, visual, and symbolic representation. In solving problem, student with low ability do not apply the look back step in two problems, and the answer obtained are wrong.